Munira Mutran & Laura Izarra. Irish Studies in Brazil - González, Rosa (ABEI Journal, 2006)
Munira Mutran & Laura Izarra. Irish Studies in Brazil. São Paulo: AssociaçãoEditorial Humanitas, 2005, 408 pages.